Relationship between cytokine single nucleotide polymorphisms and sarcoidosis among Japanese subjects - Kuroda, H.; Saijo, Y.; Fujiuchi, S.; Takeda, H.; Ohsaki, Y.; Hasebe, N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Several susceptibility genes for sarcoidosis have been identified, but their relationship to the clinical state and prognosis remains to be elucidated.The aim of this study was to elucidate the relationship between sarcoidosis and five single nucleotide polymorphisms (SNPs) of three cytokines expected to play an important role in the inflammatory response. A case-control study was performed with 208 unrelated patients who met the diagnostic criteria for sarcoidosis used in Japan since 2006, and 328 control subjects. Five SNPs were analyzed: interleukin (IL)-10-819T/C (rs1800871), IL-10-592A/C (rs1800872), IL-6-634C/G(rs1800796), tumor necrosis factor-α (TNF-α)-857C/T (rs1799724), and TNF-α -1031T/C (rs1799964). No significant differences in SNPs were observed between the total sarcoidosis and control groups. However, the prevalence of rs1800871 and rs1800872 polymorphisms differed significantly in the sarcoidosis with eye involvement group compared with the control group [rs1800871 TT (vs.TC + CC): OR = 1.67, P = 0.034; rs1800872 AA (vs. AC + CC): OR = 1.66, P = 0.036]. Analyzing the cardiac involvement group, the prevalence of the rs1799724 polymorphism was significantly different from that of the control group [rs1799724 TT (vs. CC + CT): OR = 6.01. P = 0.006].We concluded that the rs1799724 C/T polymorphism may affect susceptibility to cardiac sarcoidosis, while the rs1800871 T/C and rs1800872A/C polymorphisms may affect susceptibility to sarcoidosis with eye involvement.